2020
DOI: 10.1111/nicc.12565
|View full text |Cite
|
Sign up to set email alerts
|

Palliative care in adult intensive care units: A nationwide survey

Abstract: Background There are no data on the provision of palliative nursing care in Egyptian adult intensive care units (ICUs). The Palliative and End‐Of‐Life (PEOL) Care Index is reliable and content valid; however, its construct and criterion validities have not been examined. Aims and objectives First, to assess palliative care education, practice, and perceived competence among adult ICU nurses in Egypt. Second, to explore factors related to palliative care nursing practice and perceived competence. Third, to asse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
14
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 42 publications
1
14
1
Order By: Relevance
“…Thus, education and training programs for nurses providing EOLC should be tailored to speci c work units. ICU nurses showed increased competency in palliative care with more service training in palliative care or EOLC [41]. Previous studies observed high needs for role de nition and practice authority for advanced practice nurses [40] and a need for education [42].…”
Section: Discussionmentioning
confidence: 92%
“…Thus, education and training programs for nurses providing EOLC should be tailored to speci c work units. ICU nurses showed increased competency in palliative care with more service training in palliative care or EOLC [41]. Previous studies observed high needs for role de nition and practice authority for advanced practice nurses [40] and a need for education [42].…”
Section: Discussionmentioning
confidence: 92%
“…Thus, education and training programs for nurses providing EOLC may be tailored to specific work units. ICU nurses showed increased competency in palliative care with more service training in palliative care or EOLC [ 50 ]. Previous studies observed high needs for role definition and practice authority for advanced practice nurses [ 49 ] and a need for education [ 51 ].…”
Section: Discussionmentioning
confidence: 99%
“…Studies have indicated that those who were older had a higher level of education and had longer years of work experience had better knowledge resources as well as better skills in utilizing the resources. Nursing staff who worked at the oncology or hospice unit had more experience in care [18,19,21] and also diligently cultivated clinical talents [13]. In particular, clinical nursing staff who had participated in hospice care training had a more positive attitude towards non-ANH in terminal patients when the patient's body system deteriorates [15,21,22], and a significantly positive correlation was observed when clinical nursing staff had a better understanding of the concept of hospice care and the timing and decision-making for ANH, they had a more positive attitude towards accepting ANH [5,14,15,21,22].…”
Section: IVmentioning
confidence: 99%
“…With regard to the attitude of non-ANH to terminal patients, the difficulties as well as obstacles encountered when withdrawing ANH in clinical practice, also reveal the expectations of terminal patients and their family. This issue is a challenge [5][6][7][8][9][10][11][12][13][14]15,20,21] faced by clinical nursing staff everyday and is worth further investigation. Intervention with hospice care from the perspective of Taiwanese food culture allows further investigation of the relationships between local customs, family values and homology of medicine, food, and ANH as well as of the factors relating to these relationships, which can provide a reference for future educational strategy for clinical practice.…”
Section: Introductionmentioning
confidence: 99%